A Review on Phonetics Training Program at the Undergraduate Level of Russian Language Major in Iran: Necessities, Problems, and Solution - Saeedeh Dastamooz; Mahsa Rasouli (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the present article, Teaching Phonetic Topic in Russian Language at a bachelor degree was examined. The purpose of this study was to investigate the necessities, identify problems and provide solutions for them. The main questions are to find out the educational requirements and necessities in the field of Russian phonetic, whether these needs have been addressed in the undergraduate curriculum, and what challenges students face. In this paper, a library-based research, the nature of phonetics topics and the necessities that should be taught in this category are considered. Then field research was conducted among 140 undergraduate Russian language students. The results showed that students are weak in many phonological categories that have a direct impact on their speech. Proposals for optimizing the curriculum for phonology have been proposed to empower students.